Workplace Romance: What Indian Managers feels about it? - Amrita Sidhu,; Nazeen, Afroze; Bhalla , Pretty (International Journal of Psychosocial Rehabilitation, 2020)
In today’s industrial world the Workplace Romance is becoming a very common phenomenon in India. No matters, which type of organization it is, each and every sector where people are working together, spend their time together the Workplace Romance persists. Many previous researches have proved that it affect the organizational setting as a whole in terms of employee performance, discipline, organization culture & environment. In such a scenario it is very important to know, what Indian managers or team leaders personally feels about it. In this context , many foreign researchers found that some managers took it as positive and some of them as negative depending upon the factors like, personal thinking, organization climate (hot or cold) and types of organization (conservative or liberal). All such researches are done in foreign context, therefore the main focus of our study is to know what Indian managers personally think or feel about Workplace Romance whether positive or negative.